Sugarbeet diseases and its management - Singh, Dinesh; Vandana, Priyam; Sravani, Bana; Mall, Ashutosh K.; Pathak, A D (Indian Farming, 2019)
Sugar is produced in more than 100 countries of the world including India. With theintroduction of sugar beet in 19th century, sugarcane has been replaced by sugar beet as the mainsource of sugar in continental Europe and in the process of shifting in several other countries.Presently 40% of the world supply of sugar is from sugarbeet. Sugarbeet is considered as temperatecrop; however, it is cultivated in wide range of climatic condition due to its wide adoptability todifferent atmospheric condition. Sugarbeet contains sucrose up to 21% whereas sugarcane containssucrose up to 14% only. The sugarbeet root yield varied between 5000 and 9000 kg/h underdifferent climatic conditions. Sugarbeet is used as human food, livestock feed and for industrialuses such as in alcohol, pharmaceuticals, and baker’s yeast. This crop also has several medicinalproperties. There are several factors which affect its yield in which only sugar beet diseases arecontributing 20 to 50% yield loss and recoverable sugar reduction is up to 50% as per the diseasepressure. Numbers of bacterial, fungal and viral diseases are reported that responsible fordeterioration of sugarbeet crop either in the field condition or during storage. In this publication,importance of sugar beet and its contribution in worldwide sugar production along with the mainfocus on sugar beet diseases and its management is being discussed.